Causes of Transnational Marriage with a Home-based Spouse: Case Study from Gondare/ Ethiopians in the Diaspora - Abeje, Aschalew (Ethiopian Journal of Social Sciences, 2018)
This study analyzes the reasons why Gondare (natives of Gondar district, northwest Ethiopia) migrants choose to marry a home-based spouse. Data are collected from migrants coming home for this aim and from families through interview and questionnaire. Document analysis is used to supplement them. Although women involve considerably, findings show that men are the principal actors in suchÂ deals. This study approaches multiple experiences as intersecting mechanisms and found decisions for a marriage at home as multi-causal. It reveals that differential gender orders at the two ends set the precedence for this preference. It also shows time constraint, family pressure, desire for acknowledged marriage, and political contexts at home as important factors shaping migrantsâ€™ decisions for a home-based spouse.